A case report of monitoring PSA level changes in two prostate cancer patients treated with Mountain Ginseng Pharmacopuncture and Sweet Bee Venom along with western anticancer therapy - Yeonhee Lee; Chaewon Kim; Kwangho Lee (Korean Pharmacopuncture Institute, 2011)
Objectives: The purpose of this report is to find out how Mountain Ginseng Pharmacopuncture(MGP) and Sweet Bee Venom(SBV) treatments are effective on prostate cancer patients by monitoring Prostate specific antigen(PSA) values. Methods: We treated two prostate cancer patients with MGP and SBV from October 2008 to April 2011. One patient had localized prostate cancer, the other was in the terminal stage of prostate cancer with lung and bone metastasis and both had been receiving western anticancer therapy. We had monitored the changes of PSA value. Results: In case 1, MGP and SBV treatments seemed to be helpful in preventing the recurrence of localized prostate cancer. In case 2, PSA value was decreased by MGP treatment. Conclusions: It is conceivable that MGP and SBV are effective treatments for patients with prostate cancer.